Design & Simulation of Fractal Antenna for Wi-Max Operation - BinayBinod**, Shilpa Jain * (International Journal of Scientific Research and Management (IJSRM), 2016)
A metamaterial-based novel compact microstrip antenna is presented for Wi-Max applications. The antenna consists of a layer of metamaterial made by etching a crossed-shaped slots, on the the ground plane, respectively. The shunt inductance developed due to the patterned ground plane lead to the left-handed behaviour of the metamaterial. The proposed antenna has a compact size of 45.4 × 31.6 × 1.6  and is fed by a 50 Ω microstrip line. Radiating patch is fractal antenna of star shape with 6mm side length. The impedance bandwidth (−10 dB) is from 3 GHz to more than 14 GHz with maximum radiation in the horizontal plane and tends towards a directional pattern as the frequency increases. Maximum gain  15.8533db obtained from fractal antenna.